Worlding, Ontological Politics and the Possibility of a Decolonial IR. (June 2017) - Blaney, David L.; Tickner, Arlene B.
This article argues that attention to representational practices and epistemology, however important for expanding the boundaries of International Relations as a field of study, has been insufficient for dealing with difference in world politics, where ontological conflicts are also at play. We suggest that IR, as a latecomer to the 'ontological turn', has yet to engage systematically with 'singular world' logics introduced by colonial modernity and their effacement of alternative worlds. In addition to exploring how even critical scholars concerned with the 'othering' and 'worlding' of difference sidestep issues of ontology, we critique the ontological violence performed by norms constructivism and the only limited openings offered by the Global IR project. Drawing on literatures from science and technology studies, anthropology, political ecology, standpoint feminism and decolonial thought, we examine the potentials of a politics of ontology for unmaking the colonial universe, cultivating the pluriverse, and crafting a decolonial science. The article ends with an idea of what this might mean for International Relations.